Characteristics of Diabetes Mellitus Occurrence at RSU Imelda Pekerja Indonesia 2024 - Yuni Shanti Ritonga; Noradina Noradina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemic conditions. The hyperglycemic condition is caused by abnormalities in insulin secretion, insulin action, or both. DM is a global epidemic that causes high rates of morbidity and mortality, primarily due to microvascular and macrovascular complications. The number of diabetes mellitus (DM) patients has dramatically increased in the last 20 years. The purpose of this research is to identify the factors influencing the occurrence of Diabetes Mellitus at Imelda Pekerja Indonesia General Hospital in 2024. The research method uses a descriptive method to describe the object being studied. The research population consists of 292 with non-probability sampling using the consecutive sampling method. A sample of 40 respondents. Using a questionnaire. The research results show that out of 40 respondents, 15 respondents (37.5%) have good knowledge criteria, 24 respondents (60%) have sufficient knowledge criteria, and 1 respondent (2.5%) has poor knowledge criteria. It can be concluded that there are two factors influencing a person's knowledge: internal factors and external factors. The internal factors are education, age, and occupation, while the external factors are the environment and socio-cultural aspects.